Providing Asthma Management in the Retail Clinic Setting - Kimberly Prigge; Kelly K. Holtz; Kristin Mara; Alicia Meek (SAGE Publishing, 2022)
Objective: To determine whether there are differences in asthma management provided in the retail clinic setting versus in the primary care setting, and whether it would increase the number of well controlled asthmatics as determined by ACT score of 20 or greater, and less than or equal to 1 ED or hospital visit due to asthma, within 6 months. Methods: All asthma patients with an asthma control test (ACT) of 19 or less, received a new or updated asthma action plan (AAP) at the visit. If the patient presented to the retail clinic during an asthma exacerbation or with any asthma symptoms, they were not given an ACT and received usual care. Asthma quality data was retrospectively collected for primary care patients seen in the 6-months prior to as well as up to 6 months after the patient's enrollment visit. Results: There was no significant difference in the number of admissions between locations in either the pre-implementation period or the post-implementation period for either the pediatric or adult cohort. There was a significant improvement in the percentage of pediatric and adult patients with at least 1 ACT in the post-implementation compared to pre-implementation for both retail clinic and primary care sites. The percentage of pediatric and adult patients with at least 1 AAP increased in the post-implementation compared to pre-implementation for both retail clinic and primary care sites. Conclusion: Retail clinics may be able to provide asthma management with similar outcomes to primary care settings.